Análise das adversidades climáticas no oeste paulista e norte do Paraná - Berezuk, André Geraldo [UNESP] (Universidade Estadual Paulista (Unesp), 2007)
A análise dos modos de atuação dos mecanismos atmosféricos é uma das bases da ciência climatológica, pois, através dessas, os pesquisadores estão aptos a fazer as diagnoses regionais, as prognoses climáticas, avaliar o possível impacto de variações climáticas e desenvolver projetos para mitigá-los. Seguindo essa lógica, foi elaborada a análise de adversidade climática do oeste paulista e do norte do Paraná. Para a efetuação dessa tarefa, foi utilizada a técnica de análise rítmica de Monteiro, sendo pesquisados os anos de 1997, 1998 e 2001 nas localidades de Presidente Prudente, Maringá e Londrina. Além da pesquisa dos dados diários desses três anos, em que foram criados 108 gráficos de análise rítmica e 108 gráficos de eventos climáticos, foram analisados 27 anos de dados mensais e anuais (1976- 2003) que possibilitaram a elaboração de 54 figuras, 67 tabelas, 102 gráficos e 9 organogramas, em que foram analisadas as características atmosféricas regionais, observando possíveis tendências de alterações climáticas futuras. Foram constatados, ao longo da análise, que a área de estudo está passando por um processo de aquecimento de até 1ºC, além de um processo de fortalecimento sazonal, com as estações mais secas e chuvosas tornando-se mais bem definidas, o que pode causar, futuramente, uma maior quantidade de eventos extremos e adversidades climáticas, que, por sua vez, podem afetar as cidades e a produção agrícola.

Analyzing how the atmospheric mechanisms act is a great base of the climate science because it allows the researches to know about the regional weather aspects, to discuss the possible impact of climatic variations and to develop projects in order to protect the region against these possible variations in the soon future. Following this idea, we elaborated an analysis about hazards in the Western Sao Paolo State and the North Parana State in Brazil. We based on the Monteiro rhythm analysis method to study the cities Presidente Prudente, Maringa and Londrina in the years 1997, 1998 and 2001. Through the search of diary weather statistics we created 108 rhythm analysis graphics and 108 climatic event graphics. Besides them, we studied 27 years of mensal and annual statistics (1976 - 2003) which allowed the creation of 54 figures, 67 tables, 102 graphics and 9 examples. Through these we analyzed regional climatic aspects, searching for future tendencies of climate variations. It was verified by the analysis a warming of one Celsius degree at the studied areas and also a process of sazonalization which showed more clearly the division of wet and dry seasons. We see that it could result in the future more cases of hazards that could affect the cities and the agricultural production. The thesis revels that the climatic rhythms study, the interpretation of regional climatic variation and the study of the necessary actions to protect the areas against hazards are complex questions which involve great series of variables that, sometimes, the statistical techniques are not able to solve, despite its powerful and recognition in science. Because of that, it is extremely important the careful interpretation of climatic aspects by rhythm paradigm, mainly linking it with statistical techniques as well.
Keywords: Geografia; Climatologia; Extreme events; Hazards; Rhythm analysis